A numerical study on the influence of composite wrinkle defect geometry on compressive strength - Xie, Ningbo; Smith, Robert A.; Mukhopadhyay, Supratik; Hallett, Stephen R. (Materials & design, 2018)
Out-of-plane winkling in continuous-fibre reinforced composites has a significant influence on compressive failure stress, which needs to be considered and evaluated during the design, manufacture and inspection stages, to achieve high-performance composite components. With the development of a three-dimensional characterisation based on non-destructive testing methods and finite-element modelling, it is possible to combine the two techniques to give a prediction of mechanical performance using directly measured geometry. This paper uses a new methodology developed for combining non-destructive characterisation and numerical analysis techniques to automatically create a series of models with controlled wrinkle geometry. It has been possible to determine the dependence of compressive strength on various wrinkle-severity and wrinkle-extent parameters. The outcome shows a dominant dependence on the maximum wrinkle angle in the load direction, with an additional dependence on the wrinkle wavelength for larger wrinkle angles. In terms of the extent of the wrinkled region, the strength reduces as the wrinkle extent in the load direction becomes concentrated locally or the wrinkled proportion of the cross-sectional area (perpendicular to the load) increases. [Display omitted] •A new methodology is presented to rapidly create finite element models of wrinkled composites based on NDT information.•The suggested approach allowed a rigorous study to rank wrinkle-parameter importance using a simulator of NDT information.•Maximum angle in load direction was the key parameter affecting compressive strength, with wavelength being of secondary.•Increasing wrinkled region extent perpendicular to load direction also correlated with decreasing compressive strength.